ICT Development Index and Determinants of Service Trade: Evidence from Top Ten Exporters to Indonesia - Nurhanifah, Nurhanifah; Wardani, Dyah Titis Kusuma (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
The world is now entering the era of industrialrevolution 4.0, which emphasizes the pattern of digital economy,artificial intelligence, big data and robots or commonly known asthe phenomenon of innovation chaos. With the rapid developmentof electronics, Information and Communication Technology(ICT), better known as ICT-based electronic advances, this has animpact on international and domestic trade. There is progress inICT, in this case making distance less influential in trade. This isbecause there is no need for meetings or face-to-face meetingsbecause they have been replaced by electronic mail or cellphones.In this study, we want to examine the impact of ICT oninternational trade, especially the total service trade between theten highest service sector exporters to Indonesia. This study uses apanel data with gravity model framework for the period of 2012-2016. The results show that, ICT has a positive and significantimpact on export of ten countries services to Indonesia. Othervariables such as the GDP of the exporting country have a positiveeffect on trade service, while export destination countries havenegative effect on trade services. In addition, distance, has negativeand significant effect on service trade. This is in line with thegravity model theory, whether distance has negative relationship ontrade In this case, distance represents transportation cost. Countrycharacteristic such as openness of exporters hasa positive andsignificant effect on service trade. In contrast, openness ofdestination country has negative and significant effect on serviceexports to Indonesia